A C−N Coupling Polymerization on Ice‐Surface towards Decimeter‐Sized 2D Covalent Materials with High Catalytic Activity for Water‐Splitting. Issue 61 (9th October 2019) - Cheng, Ming; Li, Ming
Abstract: Compared to other solid templates (metal, ceramic, carbon, etc.), polymerization on ice‐surface has many advantages. However, the popularity of this method has been impeded by the lack of appropriate polymerization reactions. To date, only few oxidation polymerizations have been reported to occur on ice‐surface, and unfortunately they can only produce supramolecular films rather than fully covalent films. Herein for the first time, 2D covalent materials have been created on ice‐surface even at −16 °C through a C−N coupling polymerization, and two free‐standing 2D polyarylamines (2DPA )s were synthesized. Both 2DPA s have decimeter‐size and nanometer thickness. This study provides the first polymerization reaction to synthesize 2D covalent materials on ice‐surface, which can be used to fabricate materials/tools/robots with specific 2D structure by copying ice morphologies. Furthermore, both 2DPA s exhibit higher hydrogen evolution reaction activity than many metal‐free catalysts and even some metal‐based catalysts, so this study also provides further insight for the development of metal‐free catalysts for water‐splitting. Abstract : Cold play : A door to polymerization on ice‐surface for the synthesis of 2D covalent materials has been opened by a C−N coupling reaction. Through this polymerization, two triazine‐based 2DPA s have been synthesized, which have huge lateral size, nanometer thickness, and exhibit a higher catalytic performance of hydrogen‐evolution reaction than many metal‐free and even some metal electrochemical catalysts.